(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction: Student burnout syndrome is a major concern in higher education, associated with high prevalence rates. Its consequences include dropping out of school and adverse effects on mental and physical health. Despite this, the importance of academic engagement, a positive attitude towards learning, is often overlooked in the Moroccan context. Methods: This is a cross-sectional study conducted over a period of one month in 2023, and relies on semi-structured interviews to collect data. The measurement instruments used in this study include a self-questionnaire and two well-established scales: the Copenhagenan Burnout Inventory (CBI) and the Utrecht Work Engagement Scale (UWES-9). Results: The study reveals complex links between socio-economic factors, academic failure and burnout, with p values < 0.05. No significant relashionship was revealed between engagement and burnout (p>0.05). Female students showed a higher level of burnout than male students (p < 0.05). Age appears to be a determining factor, with younger students showing higher levels of burnout. Housing had an influence on burnout (p < 0.05) and differences between faculties showed a significant effect on burnout (p < 0.05). The internal consistency of the burnout and engagement scales are satisfactory. Conclusion: This study highlights the need for a holistic approach to addressing burnout in students. Targeted interventions are essential to support students in diverse academic contexts, taking into account a variety of socio-economic factors. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 228-236